Streaming : movies, media, and instant access - Dixon, Wheeler W., 1950- (University Press of Kentucky, 2013)
Film stocks are vanishing, but the iconic images of the silver screen remain - albeit in new, sleeker formats. Viewers can now instantly stream movies on televisions, computers, and smartphones. Gone are the days when films could only be seen in theaters or rented at video stores: movies are now accessible at the click of a button, and there are no reels, tapes, or discs to store. Any film or show worth keeping may be collected in the virtual cloud and accessed at will through services like Netflix, Hulu, and Amazon Instant. The movies have changed, and we are changing with them.